Cataract Surgery under Topical Anesthesia in a Patient with Parkinson Disease and Deep Brain Stimulation: A Report of Feasibility. Issue 3 (May 2015) - Posarelli, Chiara; Del Prete, Eleonora; Ceravolo, Roberto; Nardi, Marco; Figus, Michele
Purpose: Deep brain stimulation provides benefits for people with Parkinson disease by managing some of their complications. None of the few reports in the current literature establishes the functionality of deep brain stimulation when activated during phacoemulsification. Methods: A 70-year-old woman with subthalamic deep brain stimulator (DBS) for advanced Parkinson disease was referred to our center for cataract surgery. To evaluate any possible interference between ultrasounds and the DBS, we registered the impedance of the electrodes before and after surgery. Results: The patient underwent uneventful phacoemulsification of her right eye under topical anesthesia with her internal pulse generator device activated. During the surgical procedure, all potential variations of the impedance of the electrodes were recorded. Conclusions: This report demonstrates that phacoemulsification under topical anesthesia is a feasible procedure in patients with DBS, showing no interference between the ultrasounds and the internal pulse generator.